B‐cell‐derived IL‐10 does not vitally contribute to the clinical course of glomerulonephritis. (16th December 2013) - Kluger, Malte A.; Ostmann, Annett; Luig, Michael; Meyer, Matthias C.; Goerke, Boeren; Paust, Hans‐Joachim; Meyer‐Schwesinger, Catherine; Stahl, Rolf A. K.; Panzer, Ulf; Tiegs, Gisa; Steinmetz, Oliver M.
<x xml:space="preserve">Abstract</x> IL‐10‐secreting regulatory B cells have been postulated as negative mediators of inflammation. However, their impact on immune‐mediated diseases requires further investigation. We recently found that IL‐10‐secreting B cells infiltrate the kidney during crescentic glomerulonephritis (GN). We therefore studied the function of B‐cell‐derived IL‐10 in light of the potential risks associated with increasingly used B‐cell depleting therapies. Lack of IL‐10 production by B cells, however, did not influence acute or adaptively mediated progressive renal injury in terms of renal function and histological damage in the nephrotoxic nephritis model of GN. Renal leukocyte infiltration and cytokine expression were similar apart from increased macrophages in mice lacking B‐cell‐derived IL‐10. Systemic immune responses as assessed by cytokine production, leukocyte composition, proliferation, and activation were indistinguishable, while production and renal deposition of Ag‐specific IgG were mildly impaired in the absence of B‐cell‐produced IL‐10. Importantly, detailed analysis of systemic and renal regulatory T cells did not show any differences between nephritic mice bearing IL‐10‐deficient B cells and WT controls. Finally, studies in reporter mice revealed that B cells are only a minor source of systemic IL‐10. In summary, our data reveal that endogenous B‐cell‐derived IL‐10 does not play a major role in the nephrotoxic nephritis model of crescentic GN.